Challenges and Possibilities of Sustainable Development in Regional Government Units - Daniel Dragičević; Maja Coner; Daniel Bukovinski (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
The main goal of this article is to demonstrate whether the awareness of key actors and the application of the sustainable development concept can find appropriate solutions for the preservation of the environment in the contemporary conditions of economic development. Humanity today is facing an increase in resource utilization, climate change, environmental pollution, starvation and diseases, energy sector crises, population growth imbalances and similar challenges. For all the reasons mentioned, sustainable development model is more important than ever. This research focusses on municipalities and cities in Croatia, specifically on the concept of sustainable development and its relation to budget fiscal policy. Descriptive analysis method, comparative method and primary research method (interviews) used in this research have given the results shown in this article. Results pointed out that all the interviewees are aware of sustainable development concept and they agreed that more financial resources should be invested in this area. Furthermore, the results have shown that lifelong education is the key investing point. In addition, based on the results, there is a need for greater cooperation between state and local authority units with the goal for joint investments and projects but also for strengthening human resources in sustainable development projects.
Keywords: 650; sustainable development; local self-government units; municipality; city; fiscal policy; local development